Identification of hybrids between Neotropical fish Leporinus macrocephalus and Leporinus elongatus by PCR-RFLP and multiplex-PCR: Tools for genetic monitoring in aquaculture - Hashimoto, Diogo Teruo [UNESP]; Mendonca, Fernando Fernandes [UNESP]; Senhorini, Jose Augusto; Bortolozzi, Jehud [UNESP]; Oliveira, Claudio de [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Elsevier B.V., 2010)
Interspecific fish hybrids can represent a serious threat to the aquatic environment. Consequently, genetic monitoring of organisms that are produced by interspecific hybridization aims at the application of methodologies capable of supplying, in a clear and accessible way, the identification of hybrid individuals and their respective parental species. In the present work. molecular techniques were developed to identify the hybrid lineage of Piaupara in order to characterize them in relation to their parental species, the female Leporinus macrocephalus (Piaucu) and the male Leporinus elongatus (Piapara). Through PCR-RFLP and multiplex-PCR, analyses involving the mitochondrial 16S DNA and nuclear a-tropomyosin gene demonstrated different electrophoretic profiles between L macrocephalus and L elongatus. The nuclear gene allowed the clear distinction between the parental and hybrid individuals, since the hybrids demonstrated a heterozygous pattern with diagnostic bands inherited from both parental species. The mitochondrial DNA showed the same pattern observed in L macrocephalus in the hybrids, which can result in misidentification. The establishment of these techniques will allow the routine monitoring of the production of these hybrids in fish breeding farms and the delineation of plans for biological conservation and the proper management of the stocks. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Interspecific hybrid; Fish culture; Molecular markers; Genetic conservation